Produção, recuperação e avaliação de pectinases de Aspergillus niger LB-02-SF obtidas em biorreator de tambor rotativo - Poletto, Patrícia (My University, 2015)
In the present work, the production of pectinases by Aspergillus niger LB-02-SF in solid-state cultivation was studied using a rotating drum bench bioreactor. Furthermore, extraction and concentration of enzymes by ultrafiltration were evaluated. Formulations with the concentrated extract, KCl and glycerol were assayed with respect to the maintenance of activity level and the efficiency in the treatment of fruit juices. With respect to the production of enzymes in bioreactor, the operational parameters evaluated were agitation, cultivation temperature, occupation volume (30, 50 and 70%) and specific air flow (0.18, 0.36, 0.54, 0.72 e 0.90 LkgM – liter of air per kilogram of medium per minute). Tests without and with agitation of the bioreactor (1 rpm per 5 minutes each 120 minutes) indicated that, with occupation volume of 30%, agitation leads to increasing fungal growth and decreasing enzyme production, whereas with 50% of occupation an opposite behavior was noticed. With 70% of occupation volume, no significant difference was observed among the pectinolytic activities achieved with and without agitation, the production being hindered in both cases by the insufficient aeration of medium. The interval between agitation events was evaluated for an occupation volume of 70% and no significant difference in enzyme production was observed for the intervals of 90 and 120 minutes (standard condition). For the interval of 60 minutes, the activity was reduced in approximately 58%. The cultivations with temperature control at 34oC and without control indicated that enzyme production was favored with the natural increase of medium temperature, an aspect that could be related to a stress condition that would lead to a higher enzyme production. Specific air flows between 0.18 and 0.90 LkgM were evaluated for 30 and 50% of bioreactor occupation volume. Larger fungal growth was observed when the bioreactor was loaded with the smallest occupation volume. With the intermediate flow of 0.54 LkgM, the highest enzyme activities were achieved for both occupation volumes; however, the occupation volume of 50% resulted the higher activity of 178.2 U/g, with an activity of 133.4 U/g being measured for 30% of occupation. The results achivied indicated that for a higher enzyme production, the bioreactor should be conducted with 50% of occupation volume, specific airflow of 0.54 LkgM and interval between the agitations of 120 minutes. In the study on the extraction of pectinases from the solid medium with water pH 4, under agitation, it was observed that extraction times from 15 to 120 minutes presented similar results. The extraction temperatures of 20, 30 and 40oC did not influence protein extraction, but pectinase activity was reduced in 40% at 40oC, possibly due to the low enzyme thermostability. Among the extraction ratios of solid/liquid assessed, the value 1/10 resulted in the highest enzyme activity solubilized, with recovery of 81% of the pectinolytic activity that was present in the medium. In the concentration tests, ultrafiltration of concentrated extract with no previous treatment resulted in 59% of enzyme activity recovery and in a final permeate flux of about 11 L/m²/h. On the other hand, the operation protocol that included the use of activated charcoal, microfiltration and ultrafiltration presented enzyme recovery of 74% and final permeate flux of 24 L/m2/h, results that demonstrate the importance of pre-treatments in this process. Previously to the preparation of enzyme formulations, a volume of 30 L of enzyme extract was 103-fold concentrated by ultrafiltration, with 69% of enzyme recovery, and a final 663-U/mL extract was obtained. This concentrated extract was formulated with 20, 30, 40 and 50% (w/w) of glycerol and 2% (w/w) of KCl and evaluated for 59 weeks with respect to the enzyme activity conservation at 5ºC. At the end of the test period, the blank sample (with no additives) presented an activity decrease of 25% and also microbial contamination, whereas the formulations preserved 100% of the initial activity along the experiment. The 50%-glycerol formulation was used for Bordô grape maceration and for depectinization of apple, Rosé grape and blackberry juices, showing statistically similar results to those obtained with the commercial preparations Novozym 33095 and Pectinex Ultra SP-L used as reference. The results attained in this work pointed out to the possibility of scaling-up this process, from the enzyme production in solid-state cultivation to the achievement of an enzyme formulation that has shown potential to be used in the industry of fruit juice.
No presente trabalho, a produção de pectinases por Aspergillus niger LB-02-SF em estado sólido foi estudada em biorreator de tambor rotativo em escala de bancada. Adicionalmente, a extração e a concentração do extrato enzimático foram avaliadas. Com o extrato concentrado por ultrafiltração, formulações com KCl e glicerol foram testadas quanto à conservação da atividade enzimática e à eficiência no tratamento de sucos de frutas. Com respeito à produção das pectinases em biorreator, os parâmetros de operação avaliados foram: a agitação, a temperatura do cultivo, o volume de ocupação (30, 50 e 70%) e o fluxo específico de ar (0,18, 0,36, 0,54, 0,72 e 0,90 LkgM – litros de ar por kg de meio por minuto). Ensaios sem e com agitação do biorreator (frequência de 1 rpm por 5 minutos, a cada 120 minutos) indicaram que, para o volume de ocupação de 30%, a agitação leva ao aumento do crescimento fúngico e à redução da produção de enzimas, enquanto que com 50% de ocupação, comportamento oposto foi observado. Com 70% de ocupação, não foi observada diferença significativa entre as atividades pectinolíticas obtidas com e sem agitação, sendo que, em ambos os casos, a produção foi prejudicada pela insuficiente aeração do meio. O intervalo entre os eventos de agitação foram avaliados para o volume de ocupação em 70%, não sendo observada diferença significativa na produção de pectinases nos intervalos de 120 minutos (condição padrão) e 90 minutos. Para um intervalo de 60 minutos, a atividade reduziu-se em aproximadamente 58%. Os cultivos com controle de temperatura em 34oC e sem controle indicaram que a produção enzimática foi favorecida com a elevação natural da temperatura do cultivo, um aspecto que pode estar relacionado a uma condição de estresse que levaria à maior produção enzimática. Fluxos específicos de ar entre 0,18 e 0,90 LkgM foram testados em ensaios com 30 e 50% de volume de ocupação do biorreator. Maior crescimento fúngico foi atingido quando o biorreator foi carregado com menor volume de ocupação. Com o fluxo intermediário de 0,54 LkgM, as maiores atividades enzimáticas para ambos os volumes de ocupação foram atingidas; porém, a ocupação de 50% do volume resultou na maior atividade pectinolítica, 178,2 U/g, com uma atividade de 133,4 U/g sendo medida com 30% de ocupação. No estudo sobre a extração de pectinases do meio sólido, com água pH 4, sob agitação de 200 rpm, foi observado que tempos entre 15 e 120 minutos apresentaram resultados similares. Os resultados atingidos apontam que para maior produção enzimática o biorreator deve ser operado com 50% de ocupação, fluxo específico de ar de 0,54 LkgM e intervalos entre as agitações de 120 minutos. Temperaturas de extração de 20, 30 e 40oC não influenciaram na extração de proteínas, porém a atividade de pectinases foi reduzida em 40% a 40oC, possivelmente em razão da termoestabilidade da enzima. Entre as razões de extração sólido / líquido avaliadas, o valor de 1/10 foi a que resultou na maior atividade enzimática solubilizada, sendo recuperados 81% da atividade pectinolítica presente no meio. Nos ensaios de concentração, a ultrafiltração do extrato concentrado sem qualquer tratamento prévio resultou em recuperação de 59% das enzimas e em fluxo final de permeado da ordem de 11 L/m2/h. Por outro lado, o protocolo de operação que incluía o uso de carvão ativado e microfiltração, apresentou recuperação de enzimas de 74% e fluxo final de permeado de 24 L/m2/h, demonstrando a importância dos pré-tratamentos na ultrafiltração. Previamente à preparação das formulações enzimáticas, um volume de 30 L de extrato bruto foi concentrado 103 vezes por ultrafiltração, com recuperação enzimática de 69%, e um extrato com 663 U/mL foi obtido. Este extrato concentrado foi formulado com 20, 30, 40 e 50% (m/m) de glicerol e 2% (m/m) de KCl e avaliado, por 59 semanas, quanto à conservação da atividade a 5°C. Ao final do período de teste, a amostra controle (sem aditivos) teve queda de 25% da atividade além de apresentar contaminação microbiana, enquanto as formulações mantiveram a atividade em torno de 100% durante todo o experimento. A formulação com 50% de glicerol foi utilizada na maceração de uva bordô e na despectinização de sucos de maçã, uva rosada e amora, demonstrando comportamento similar aos encontrados com as preparações comerciais Novozym 33095 e Pectinex Ultra SP-L utilizadas como referência.
Keywords: Enzimas; Pectinase; Aspergillus niger; Suco de frutas - Indústrias; Enzymes; Pectinase; Aspergillus niger; Fruit juices - Industries